Dampak Covid-19 Terhadap Pendapatan Petani Padi Sawah (Oryza sativa) di Desa Samal Kecamatan Seram Utara Timur Kobi - Hermawanti, Eka; Timisela, Natelda R; Parera, Waldemina B (Universitas Pattimura, 2023)
This study aims to determine the impact of Covid-19 on farmers' income. The analysis used is the Wilcoxon test and the results are farmer income of IDR 5,841,317 before Covid-19 and IDR. 2,700,207 during Covid-19. The results of the different tests showed that there were significant differences in the income levels of rice farmers before and during the Covid-19 period. The results of the different tests showed that there were differences that were relevant to the income level of paddy rice farmers before and during the corona virus.